Intersections of Literacy and Teaching With the Disciplines and Professions: We Asked Some Experts. Issue 3 (25th October 2019) - Wolsey, Thomas DeVere; Lapp, Diane; Grant, Maria C.; Karkouti, Ibrahim M.
Abstract: A project to invite experts in various disciplines to converse with literacy professors and teachers with over 30 participants resulted in several insights about disciplinary literacy and student learning in the disciplines and professions. The authors suggest that such conversations or partnerships strengthen student learning for college, career, and civic life. The authors differentiate between professions and disciplines, highlighting how informed citizenship is an important outcome of teaching the literacies of the disciplines. The authors explore the purposes of communication within and between the disciplines. Insights and recommendations are presented.